The role of urban green space design to support bird community in the urban ecosystem (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Prihandi DR, Nurvianto S. 2022. The role of urban green space design to support bird community in the urban ecosystem. Biodiversitas 23: 2137-2145. The increase in human population due to urbanization causes the expansion of urban areas that threatens forest lands to be lost and makes a serious threat to its biodiversity. Along with changes in the landscape due to urbanization, open green space is an alternative solution to maintaining biological diversity in urban areas. However, various types of open green spaces were developed following certain objectives of landscape management that potentially have different effects on biodiversity. This research aimed to identify the role of various open green spaces designs on bird biodiversity. Birds can be a good indicator of environmental quality because birds are a type of animal that can move in different habitat types and habitat areas and are often used as an indicator of habitat quality in urban areas. Bird observation was conducted using the point count method, while the environmental conditions were recorded using the nested and protocol sampling method. Those data were collected in five different open green spaces of Daerah Istimewa Yogyakarta Province. Species diversity shows the diversity of species in a bird community in a certain area using the Shanon-Wiener index. Bird communities were also analyzed using rarefaction analysis. This analysis was used to standardize the species abundance in each type of green open space to estimate the ideal species richness of open green space from the different number of samples. The Kruskal-Wallis test was used to compare the value of diversity, richness, and relative abundance of bird species among five different types of open green space. We used Canonical Correspondence Analysis (CCA) to visualize the bird's response toward environmental gradients. Generalized Linear Model (GLM) was employed to determine the effect of the environmental factors on the diversity of bird species. The result showed that different types of urban green spaces have different richness and relative abundance of bird species. We found 5925 individual birds from 40 species in five different types of open green spaces. The garden was the type of open green space with the highest bird species diversity. Of the many variables taken, the slope and the number of vehicles per minute affected the diversity of species. Those two variables were also negatively correlated with the diversity of bird species in the five types of open green spaces. The number of vehicles causes noise and pollution, which causes a decrease in bird populations. Flat slopes can also help birds get food, such as seeds on a flat surface. Creating more gardens for public and private spaces becomes an alternative solution to enhance bird diversity in the urban area.